Bridging performance based seismic design with restricted interventions on cultural heritage structures. (1st April 2018) - Spyrakos, Constantine C.
Highlights: A methodology is presented to design interventions to heritage structures. It bridges seismic safety with feasibility of interventions on monuments. The procedure allows application of less extended interventions and re-evaluation. Seismic hazard is considered utilizing attenuation equations. The notion of "nominal life of intervention, ΤΔ ", is introduced. Abstract: There is lack of a common approach to assess seismic risk of historic structures and monuments. The challenge of balancing safety with maintenance of architectural and artistic features of historic structures remains a pressing issue. In many cases limitations, stemming from the implementation of interventions on historic structures and monuments that do not comply with internationally accepted guidelines do not allow for heritage structures to fulfill the performance level of new constructions for the required probability within a specific conventional life that is usually defined by seismic codes. Earthquake protection of cultural heritage structures can be realized through a preventive knowledge of the seismic risk in order to plan mitigation strategies and schedule the necessary strengthening measures to reduce vulnerability. Strengthening of cultural heritage structures in order to meet the requirements of contemporary seismic codes often requires invasive interventions that may not be applied because of relevant limitations. This work presents a methodology that leads to interventions balancing the demands of security to seismic hazard with respect for the cultural and archaeological characteristics of the structure. Following the proposed methodology rehabilitation measures are designed for a specific performance level that is associated to a certain nominal life, after which the structure should be re-evaluated. Utilizing attenuation equations, it arrives at a simple to apply procedure and diagrams that can be used to evaluate and design interventions to heritage structures. The application of the method is demonstrated with a historic structure in north-eastern Greece. The analysis shows that after the application of all acceptable interventions the strengthened structure could not fulfill the performance level of a new structure. The proposed methodology allows the determination of the nominal life of the applicable interventions after which structural integrity should be re-examined.